DELINEATING TOXIC MASCULINITY IN TANA FRENCH’S THE WITCH ELM - Ikbarfikri K., Abiyyu (Rubikon : Journal of Transnational American Studies, 2024)
This article explores the concept of toxic masculinity in The Witch Elm (2018), a novel by Tana French, using R.W. Connell's theory of hegemonic masculinity and Amy Wharton's sociology of gender frameworks. The research focuses on the protagonist, Toby, who shows toxic masculine traits such as emotional suppression, independence, aggression, and vulnerability avoidance. The study uses qualitative descriptive analysis, examining key scenes in the novel in which these behaviors manifest, especially in relation to family and romantic partners. Through this analysis, the findings reveal how toxic masculinity not only contributes to Toby's deteriorating mental health but also isolates him emotionally, resulting in damaged relationships and increased psychological distress. Ultimately, the article concludes that toxic masculinity extends emotional isolation, reinforcing harmful gender norms that prevent men from seeking support or expressing vulnerability. The research contributes to a broader discourse on how societal expectations of masculinity negatively impact individual males while continuing gender inequality. The study highlights the importance of challenging these norms to foster healthier emotional expression, stronger relationships, and more fair gender dynamics in society.